Sarkofag. Wirtualne istnienie i realne nieistnienie - Huculak, Łukasz (Wydział Sztuki UR, 2017)
The article deals with the significance of the vanitas theme in visual arts and considers its controversial status in contemporary culture. The beginnings of civilization are connected with burying rituals and the need to commemorate the ancestors: we date particular communities according to the first burials, regarding their attitude towards the infirm as an indicator of socialization and the attitude towards the dead as a source of symbolic thinking, i. e. a manifestation of high culture. Compared with the periods during which those customs developed and consolidated, the present era seems to be distinguished by a certain serenity: we have managed to camouflage the prospect of the end with hygiene and cosmetics and postpone the moment of dying by means of medicine and entertainment. Real death has therefore gained an acceptable look and the remains of the terror vanish with the universality of virtual dying (films, games, news bulletins).
Sarcophagus. Virtual being and real non-being
Keywords: epitafium; czaszka; śmierć; pogrzeb; nagrobek; klepsydra; sarkofag; vanitas; skull; death; burying rituals; virtual dying; camouflaging death; hourglass; sarcophagus